The unique and conditional effects of interoceptive exposure in the treatment of anxiety: A functional analysis. (June 2019) - Boettcher, Hannah; Barlow, David H.
Abstract: Interoceptive exposure (IE; exposure focused on anxiety about somatic sensations) is a well-established component of treatments for panic disorder (PD), but little is known about the specificity of its effects or individual response patterns resulting from this intervention. This study investigated the utility of IE in the treatment of PD with claustrophobia, examining its mechanisms in isolation and in combination with situational exposure. Ten adults with PD and claustrophobia were treated with a flexible single-case approach. Participants received up to 6 sessions of IE; nonresponders received up to 6 additional sessions of IE combined with situational exposure. Hypotheses were: 1) Reductions in anxiety sensitivity (AS) and fearful expectancies would coincide with the introduction of IE and reach clinical significance by the end of the IE phase; 2) Reductions in claustrophobic avoidance would coincide with the introduction of situational exposure; 3) Fear extinction and distress habituation would occur in both intervention phases. Hypothesis 1 was not supported: Five participants experienced a reduction in AS and six participants experienced reduced expectancies of feared outcomes, but this did not reliably coincide with introduction of IE. Hypothesis 2 was supported: Claustrophobic avoidance improved more after the addition of situational exposure. Hypothesis 3 was supported: Habituation and fear extinction, whereby distress and expectancies of feared outcomes decreased and fear tolerance increased, were observed in response to IE delivered alone and in combination with situational exposure. IE appeared more helpful to participants who were fearful of the physical consequences of somatic sensations (e.g., heart attack) vs. other consequences (e.g., embarrassment). The observed variability in response to IE suggests a need for individualized implementation of this intervention. Highlights: IE does not consistently lead to clinically significant improvement in AS for individuals with panic disorder and claustrophobia. IE alone does not reduce claustrophobic avoidance. IE alone is most beneficial to individuals whose panic-related fears are intrinsic to physical arousal (e.g., heart attack) and is not sufficient for individuals whose fears have additional extrinsic components (e.g., humiliation). Adding situational exposure to IE has incremental benefit for some patients. Both IE and combined IE + situational exposure result in patterns of fear extinction whereby distress decreases, expectancies of feared outcomes decrease, and subjective fear toleration increases across exposure trials.